Angels, Putti, Dragons and Fairies: Believing the Impossible - Roger Wotton (Opticon1826, 2009)
Representational art - painting, cartoon film, etc. - makes myths appear real, with mythological creatures and objects often placed within familiar and naturalistic scenes. We are then witnesses to events that may be described only in literature, or in verbal folklore, yet the images created become believable. In this way the myths are reinforced and we assimilate these fantastic forms into our thinking. One of the myths is that of flying beings. Angels, putti, fairies and dragons are all shown as having wings, an otherwise naturalistic form that we recognise readily. Yet, are they able to fly? If not, why do we wish to suggest they have the same powers of flight as real flying animals?
Keywords: mythology; folklore